An Assessment of the Motivational factors and Characteristics of Women Entrepreneurs in the Construction Industry in South Africa: Array - Aneke, Evelyn Omayemi; Derera, Evelyn; Bomani, Mapeto; Ganiyu, Idris Olayiwola (The Journal of Accounting and Management, 2021)
The construction industry is noted to be male dominated. Despite the male dominance of the industry, women entrepreneurs have been observed to be establishing their presence and have survived over the years. This study intends to fill this gap by examining the factors motivating the women entrepreneurs to establish small businesses in the construction industry in South Africa. This study contributes to the body of knowledge on women entrepreneurs operating small businesses in the construction industry. The main aim of this study is to examine the factors that motivated the women entrepreneurs to establish small businesses in the construction industry and the characteristics that have made them survive in a male-dominated industry. The study adopted a qualitative research approach in which empirical evidence was collected through in-depth interviews from sixteen women entrepreneurs who operated in the construction industry. NVivo 12 software was used to conduct thematic analysis. The results revealed that women entrepreneurs are motivated by several factors to venture into the construction industry. These factors include the need to empower themselves and the community, the need to challenge patriarchy, the need for independence, the need for money, and wealth creation among others. The implication for practice was derived from the outcome of the analysed data which suggests that women would continue to survive in the construction industry as long as they have the right motivation.